Management of a virtual social network: Impact on university mathematics - Chávez Márquez, Irma Leticia (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The objective of the research work was to evaluate the relationship between the use of a social network and academic performance in the subject of mathematics. For the research method, we worked with a sample of 570 students enrolled in the subject of mathematics, which was divided into strata. It was carried out in a public university in the north of Mexico. The research was longitudinal and correlational. The main results indicate that the greater academic interaction in a social network, the better academic performance in mathematics. This may be applicable for exact sciences in Higher Education Institutions.